2008
DOI: 10.4315/0362-028x-71.5.908
|View full text |Cite
|
Sign up to set email alerts
|

UV Light Inactivation of Hepatitis A Virus, Aichi Virus, and Feline Calicivirus on Strawberries, Green Onions, and Lettuce

Abstract: A majority of illnesses caused by foodborne viruses are associated with fresh produce. Fruits and vegetables may be considered high-risk foods, as they are often consumed raw without a specific inactivation step. Therefore, there is a need to evaluate nonthermal treatments for the inactivation of foodborne pathogens. This study investigates the UV inactivation of three viruses: feline calicivirus (a surrogate for norovirus), and two picornaviruses, hepatitis A virus and Aichi virus. Three produce types were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 30 publications
2
68
1
Order By: Relevance
“…Nevertheless, for viruses inoculated on lettuce, the viral decline was indeed lower. This result, being consistent with some previous studies (16,27), indicates that due to the sheltering or inaccessibility of the food structures, the interfering effect of real food might be too complicated to be simulated by one simple protein.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, for viruses inoculated on lettuce, the viral decline was indeed lower. This result, being consistent with some previous studies (16,27), indicates that due to the sheltering or inaccessibility of the food structures, the interfering effect of real food might be too complicated to be simulated by one simple protein.…”
Section: Discussionsupporting
confidence: 92%
“…However, this system is rather complex and not yet confirmed by other groups; therefore, surrogate viruses that share common pathological and/or molecular features with human NoVs are used instead. Feline calicivirus (FCV) and coliphage MS2 were almost exclusively used as a surrogate virus in previous studies (1,10,16,36). In 2003, a NoV that infects mice, namely, murine norovirus 1 (MNV-1), was identified (23).…”
mentioning
confidence: 99%
“…Due to the lack of suitable animal models and the inability to propagate in cell cultures for human NoVs (4), surrogates that share pathological and/or biological features with human NoVs have been used to study the inactivation of human NoVs (8,9,17). MNV-1 has been used since it is cultivable and belongs to the same genus as human NoVs (34).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of inactivation of infectious human NV in food are rare. Various inactivation studies have been performed with FCV (17,28,32,35,68,82,86) and murine norovirus (7,8,10,11,21,51), which are cultivable viruses belonging to the family Caliciviridae with ssRNA, as models for NV. The findings of these studies cannot be directly applied to NV because several results indicated that the surrogates are generally more sensitive to physicochemical treatments (21,57).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies are limited mainly to shellfish (42,43) and berries (18,19) or to cultivable enteric viruses, such as hepatitis A virus (HAV) (15,24,42,66,78), poliovirus (PV) (26,84), or rotavirus (12). Due to the lack of a mammalian cell culture or animal model for norovirus, various studies of persistence and inactivation have been performed with genetically related surrogates of norovirus, including feline calicivirus (FCV) (17,28,32,35,68,82,86) and murine norovirus (MNV) (7,8,10,11,21,51), which are cultivable nonenveloped viruses belonging to the family Caliciviridae. However, the validity of data obtained with these surrogates is limited because these viruses appear to be generally less stable than human NV when they are subjected to physicochemical treatments (21,57).…”
mentioning
confidence: 99%